Tailoring the dispersibility of non-covalent functionalized multi-walled carbon nanotube (MWCNT) nanosuspension using shellac (SL) bio-resin: Structure-property relationship and cytotoxicity of shellac coated carbon nanotubes (SLCNTs) - Moshiul Alam, A. K. M.; Beg, M. D. H.; R. M., Yunus; Islam, M. R.; Shubhra, Quazi T. H. (Elsevier, 2021)
This study first reports the use of natural thermoplastic bio-resin shellac (SL) to functionalize multi-walled carbon nanotubes (MWCNTs). The MWCNTs were coated with 5, 10, and 15 wt% SL solutions to fabricate SLCNT nanocomposites which are highly dispersible and stable in solution. Enhanced surface charge imparted long-term stabilization of SLCNT nanosuspension. Microscopic analysis revealed distinct dispersion of nanotubes and a thin layer of SL on the surface of nanotubes in the nanocomposite system. FTIR and Raman spectroscopy confirmed well interaction between SL and MWCNT in the nanocomposites. It was disclosed by the microstructure analysis that the SL concentration affects the lattice parameters of SLCNT nanocomposites. The thermal stability of SLCNT was impressive compared to MWCNT. According to the ROS (reactive oxygen species) generation profile and cell viability study, SLCNTs have reduced adverse effects on cells. Therefore, the results confirm that shellac can significantly improve the stability of MWCNT and reduce the cytotoxicity to facilitate their widespread applications.